THEORETICAL AND PRACTICAL FEASIBILITY OF APPLICATION OF INTERNATIONAL EXPERTISE OF REGIONAL ECONOMIC POLICY IN ARMENIA (Proceedings of the YSU C: Geological and Geographical Sciences, 2020)
The article is dedicated to the elucidation of feasibility of application in the RA of the theoretical models of regional economic policy by leading countries and, in this context, the efficiency of on-going programs in the country.
Keywords: regional economic policy; uneven development; polarized development; community budget; poles and centers of growth